The Linkage Between Work Unit Performance Perceptions of U.S. Federal Employees and Their Job Satisfaction: An Expectancy Theory - Soyoung PARK; Sungchan KIM (Transylvanian Review of Administrative Sciences, 2017)
Public organizations are interested in how to improve their performance. Performance in a work unit can also influence employee job satisfaction due to positive expectations based on higher performance. Thus, our study attempts to investigate if organizational performance has an impact on employee motivation under the premise that employees who perform better in a work unit expect greater professional recognition and rewards. By using data from the 2013 Federal Employee Viewpoint Survey (FEVS), we find that employees who perceive higher levels of performance in a work unit have a higher level of job satisfaction. This paper further shows that performance perception based on rewards is also positively related to job satisfaction. However, underrepresented groups (female and non-white), older employees and mid-level (work experience from 6 to 14 years) employees are less satisfied with higher work unit performance. Finally, employees in the distributive agency category are more satisfied with work unit performance while those in the regulatory agency category are less satisfied with work unit performance. In conclusion, organizations should recognize particular characteristics of employees to develop the policies related to performance management, and effectively utilize these policies in order to attract and retain proficient workers.